Reviewing and Criticizing the Book “Europe since Napoleon” - Hossein Pendar (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The book "Europe since Napoleon" is a thorough book regarding liberal European history (not European liberal history) written by David Thomson, an English liberal-political philosopher, whose negligence of a significant point challenges his historical attitude on European history despite his insistence on a liberalist stance in explaining, criticizing and reviewing an integrated history of Europe, which takes its historical heritage from unifying elements. Thomson believes that understanding modern "European history" is only possible through studying the pervasive forces that have been influential on its formation from Britain to the Balkans over time. Therefore, he emphasizes a broad range of factors such as population growth, industrialization, overseas development, democracy, socialism and nationalism, and the war-revolution relationships. Thomson investigates these factors, not country by country, but step by step in the spirit of Europe whole, until its civilization and culture formation over the last two centuries. However, scrutinizing the above statement indicates Thomson's negligence of the set of factors that pave the way for a modern Europe.